Pendampingan Perilaku Usaha Peternak Sapi Perah dalam Peningkatan Kesejahteraan Masyarakat - Purmiyati, Atik (Universitas Muhammadiyah Malang, 2024)
Purpose – This community service aims to increase local economic potensial and implement one of objectives of the Sustainable Development Goals (SDG’s), namely improving community welfare by analysing the weaknesses and strengths of micro businesses run by the Palangsari Village community. Design/methodology/approach – This community service using SWOT analysis techniques with IFAS and EFAS for analysing the weaknesses and strengths of micro businesses run by the Palangsari Village community. Findings – Based on the results of the SWOT analysis accompanied by IFAS and EFAS analysis, it shows that the economic position of Palangsari Village is in quadrant 1. Therefore, action is needed to maintain the position of Palangsari village in quadrant 1 by increasing its strenghts and reducingf its weaknesses. Increasing the strenghts of Palangsari Village can be done through promotional activities for products processed by local communities. Meanwhile, strenghtening the potential of the dairy farming sector can be done by improving the quality of human resources for village development and processing local products. Originality/value – This Partnership program with the community helps the service team carry out training, manage and market processed village product, especially dairy cow milk from Palangsari Village.